The Use of Video Tutorial in Increasing Understanding of Ceramic Tiles Installation for Walls and Floors in the Subjects of Building Construction Basics - Suriyanto, Suriyanto; Handayani, Sri (Universitas Negeri Semarang, 2020)
The building construction basics include the installation of ceramic tiles for walls and floors as the primary topic. However, using conventional methods as instructional media has caused a lack of understanding for some students, especially for beginner students, as they will face difficulty imagining the material presented. Moreover, the students would hardly see the detailed installation demonstrations and tend to get bored with explanations through whiteboards. Creating video tutorials is one alternative to make it easier for students to understand and know the technique of installing wall and floor tiles. This study employed a Research and Development (R&D) approach, and a Four-D model was utilized in the video tutorial making. The feasibility test phase involved student respondents and expert instructors, including three instructors from P4TK VEDC of Malang and 98 tenth-grade students of SMK 2 State Vocational High School in Pati. The results of the analysis of the students’ material needs found 64.3% or more than half of the students did not understand the topic of ceramic installation. Further, the test results from content experts and media experts obtained percentages of 93.5% (very feasible) and 83% (feasible), respectively. The test of understanding the material by students obtained a percentage of 77% (good). The study concluded that the video tutorials for installing wall and floor tiles are suitable for use in learning activities as the learning outcomes have proven that students have good understanding skills in ceramic installation. The innovation of instructional media becomes the novelty of this research. The study has applied video tutorials demonstrated by international experts by adopting the World Skills International ceramic installation competency standard, namely the paste system.